PERCEPTION OF ORGANIZATIONAL POLITICS AND JOB-RELATED NEGATIVE EMOTIONS AS PREDICTORS OF WORKPLACE INCIVILITY AMONG EMPLOYEES OF DISTRESSED BANKS - Bolanle Ogungbamila (European Scientific Journal, ESJ, 2013)
This study extents the literature on workplace incivility by investigating the extent to which perception of organizational politics and job-related negative emotions predicted workplace incivility. Participants were 248 employees (121 males; 127 females) of distressed commercial banks, whose ages averaged 27.43 years (SD=9.58). Results indicated that marital status predicted workplace incivility such that employees that were single tended to be less civil than those that were married. Academic qualification also exerted influence on workplace incivility such that workplace incivility reduced as employees’ level of education increased. Employees who perceived organizational politics also tended to engage in workplace incivility. Job-related negative emotions significantly predicted workplace incivility in such a way that employees who felt bad about their jobs tended to exhibit workplace incivility. Workplace violence might be employees’ negative way of coping with self-serving behaviors and other negative work situations.